2009
DOI: 10.1093/jac/dkp427
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of Acinetobacter baumannii RND efflux transporters in mediating decreased susceptibility to biocides

Abstract: This is the first study demonstrating the role of efflux pumps in mediating decreased susceptibility to disinfectants and other chemical substrates in A. baumannii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 8 publications
10
87
0
1
Order By: Relevance
“…1 and Table S2). The AdeABC efflux system has been shown to mediate resistance to chlorhexidine in clinical A. baumannii isolates (6). Studies conducted in P. aeruginosa and Burkholderia cenocepacia have shown that overexpression of homologous RND efflux systems is a major part of the transcriptional response to chlorhexidine stress (9, 10), indicating that these proteins are primary chlorhexidine resistance factors across a number of Gram-negative genera.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table S2). The AdeABC efflux system has been shown to mediate resistance to chlorhexidine in clinical A. baumannii isolates (6). Studies conducted in P. aeruginosa and Burkholderia cenocepacia have shown that overexpression of homologous RND efflux systems is a major part of the transcriptional response to chlorhexidine stress (9, 10), indicating that these proteins are primary chlorhexidine resistance factors across a number of Gram-negative genera.…”
Section: Resultsmentioning
confidence: 99%
“…AdeIJK contributes to both intrinsic and acquired MDR (502, 528,530,533,542,543). Its inactivation in a wild-type strain caused mostly 4-to 16-fold reductions of MICs of ␤-lactams (aztreonam, ceftazidime, cefepime, and ticarcillin), chloramphenicol, clindamycin, erythromycin, fluoroquinolones (norfloxacin and ciprofloxacin), and tetracyclines (tetracycline, minocycline, and tigecycline) (184,542).…”
Section: Acinetobacter Sppmentioning
confidence: 99%
“…Its inactivation in a wild-type strain caused mostly 4-to 16-fold reductions of MICs of ␤-lactams (aztreonam, ceftazidime, cefepime, and ticarcillin), chloramphenicol, clindamycin, erythromycin, fluoroquinolones (norfloxacin and ciprofloxacin), and tetracyclines (tetracycline, minocycline, and tigecycline) (184,542). AdeIJK also mediates resistance to biocides, including the frequently used biocides chlorhexidine and triclosan and other disinfectants in hospitals (530,544). In vitro selection of AdeIJK-overproducing mutants by triclosan was recently demonstrated (544).…”
Section: Acinetobacter Sppmentioning
confidence: 99%
“…Besides, nonenzymatic mechanisms, like modifications of antibiotic membrane permeability, usually act in synergy with these enzymes to confer a high-level resistance phenotype (18,20,53,60). These permeability modifications could be to the overexpression of multidrug RND efflux pumps (12,33,34,47,48,50,57) and/or modifications of outer membrane protein (OMP) expression or structure (9,29,30,39,40,42,54).…”
mentioning
confidence: 99%